Science and special education teachers create inclusive classroom practice in science - Jamil Suprihatiningrum; Carolyn Palmer; Carol Aldous (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2022)
The purpose of this research was to examine how co-teachers collaborate interdependently to make the science classroom inclusive for all students. Seven participants; two science teachers of School Smart; two science teachers of School Brainy; support teachers of School Smart and Brainy respectively; and Lily, the head of the inclusion program of School Brainy were selected purposively. As a qualitative description study, data were collected through semi-structured interviews, classroom observations, and instructional document analysis. Data collected were analyzed through a deductive approach using co-teaching as a predetermined framework. The findings indicate that the co-teachers in two schools were teaching collaboratively through co-planning, co-instructing, and co-assessing. Co-teachers from both schools claimed that most of the time spent collaborating was on co-instruction rather than co-planning and co-assessment. In School Smart, the co-teaching between science and the support teacher, called an alternative teaching model, is operating more effectively in terms of planning, scheduled meetings to discuss instructional planning and its implementation compared to School Brainy. Co-teachers in School Smart work more interdependently and collaboratively than the co-teachers in School Brainy